All Days 2011
DOI: 10.2118/149591-ms
|View full text |Cite
|
Sign up to set email alerts
|

Applicability and Assessment of Micro-Wave Assisted Gravity Drainage (MWAGD) Applications in Mehsana Heavy Oil Field, India

Abstract: Exploitation of extra heavy oil resource will be the main R & D challenge in the future. In India Mehsana oil field is the one of the extra heavy oil belts. In such type of fields advanced EOR is of primary concern to increase the recovery. Apart from conventional thermal methods this paper discusses about the commercialization and broad application of (MWAGD) as alternative thermal method in the Mehsana oil field. In this study, applicability of microwave heating for heavy oil from Mehsana heavy oil field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Jha et al [27] proposed using microwave-assisted gravity drainage (MWAGD) in the Mehsana oil field in India. They heated specially prepared samples with the required characteristics from that field in the laboratory using a microwave with variable power up to 1000 watts operating at 3 GHz frequency, which allowed them to obtain temperature and viscosity profiles of the gravity-drained oil.…”
Section: Review Of Experimental Electromagnetic Heat Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Jha et al [27] proposed using microwave-assisted gravity drainage (MWAGD) in the Mehsana oil field in India. They heated specially prepared samples with the required characteristics from that field in the laboratory using a microwave with variable power up to 1000 watts operating at 3 GHz frequency, which allowed them to obtain temperature and viscosity profiles of the gravity-drained oil.…”
Section: Review Of Experimental Electromagnetic Heat Studiesmentioning
confidence: 99%
“…Jha et al [27] suggested using MWAGD commercially by drilling one horizontal well and multiple vertical ones with downhole microwave antennas. However, this might not allow deep enough heat penetration, so other options are also proposed such as a combination of two horizontal wells and installing antenna inside the horizontal production well.…”
Section: Review Of Experimental Electromagnetic Heat Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Johnson et al (1992) performed history matching with steamflooding in the Kern River field in California, optimizing formation-temperature, fluid, and permeability parameters with the relative permeability parameters corresponding with the data from laboratory experiments. Hiebert et al (2013) performed assisted history matching for a steam-assisted-gravity-drainage simulation incorporating 4D-seismic data.…”
Section: Introductionmentioning
confidence: 99%